High-calorie diet partially ameliorates dysregulation of intrarenal lipid metabolism in remnant kidney - Kim, Hyun Ju (2009)
Chronic renal failure (CRF) is associated with malnutrition and renal tissue accumulation of lipids, which can contribute to progression of renal disease. This study was designed to explore the effect of a high-calorie diet on pathways involved in lipid metabolism in the remnant kidney of rats with CRF. 5/6 nephrectomized rats were randomized to receive a regular diet (3.0 kcal/g) or a high-calorie diet (4.5 kcal/g) for 12 weeks. Renal lipid contents and abundance of molecules involved in cholesterol and fatty acid metabolism were studied. The CRF group consuming a regular diet exhibited growth retardation; azotemia; proteinuria; glomerulosclerosis; tubulointerstitial injury; heavy lipid accumulation in the remnant kidney; up-regulation of lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1), ATP-binding cassette transporter-1 (ABCA1), liver X receptor (LXR) α/β, carbohydrate-responsive element binding protein (ChREBP) and acyl-CoA carboxylase (ACC); and down-regulation of peroxisome proliferator-activated receptor-α (PPAR-α), carnitine palmitoyltransferase-1 (CPT1) and liver-type fatty acid binding protein (L-FABP). The high-calorie diet restored growth; reduced the severity of tubulointerstitial injury, proteinuria and azotemia; partially lowered renal tissue lipid contents; attenuated the up-regulation of mediators of lipid influx (LOX-1), lipid efflux (LXR-α/β and ABCA1) and fatty acid biosynthesis (ChREBP and ACC); and reversed the down-regulation of factors involved in fatty acid oxidation (PPAR-α, CPT1 and L-FABP). In conclusion, a high-calorie diet restores growth, improves renal function and structure, and lowers lipid burden in the remnant kidney. The latter is associated with and most likely due to reduction in lipid influx and enhancement of fatty acid oxidation.